Public Complaint Service via the Helpdesk Website of KPU Wajo Regency Towards the 2024 Election - Jaelani, Riyan; Asparill, Teguh Ahmad (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This study aims to improve public understanding of the KPU Helpdesk website for submitting complaints during the 2024 election, addressing issues in data verification and promoting more effective use of the platform.Method: Direct assistance was provided to guide the public in navigating the KPU Wajo Regency Helpdesk website, filling out forms, and uploading documents.Practical Applications: The findings help enhance the accessibility and usability of complaint services, supporting more accurate data verification and active public participation in the election process.Conclusion: The study showed high public enthusiasm for submitting complaints and increased participation in minimizing data errors, highlighting the value of user support for better election management.